MANAJEMEN LABA, TATA KELOLA DAN NILAI PERUSAHAAN - SHEVIN WINARTA; IRENE NATALIA; DEDHY SULISTIAWAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to empirically determine the effect of earnings management and corporate governance practices on firm value. Modified Jones-based discretionary accruals are used as a proxy for earnings management. Firm value is measured by Tobin's Q and corporate governance is evaluated by independent commissioners, managerial ownership, institutional ownership, and auditor reputation. The study uses companies listed in Indonesia Stock Exchange for the 2017-2019 period. The main findings indicate that earnings management has a positive effect on firm value and institutional ownership is able to weaken the effect of earnings management on firm value. This study contributes to market-based accounting research and corporate governance.